Twin boundary fatigue crack nucleation in a polycrystalline Nickel superalloy containing non-metallic inclusions. (March 2022) - Bergsmo, Alexander; Xu, Yilun; Poole, Benjamin; Dunne, Fionn PE
Abstract: Non-metallic inclusions and twin boundaries are preferred fatigue crack nucleation locations in polycrystalline Ni-based superalloys. A Heaviside HR-DIC, EBSD and multi-scale modelling strategy (CPFE-DDP) was used to assess experimental observations of fatigue crack nucleation near agglomerated inclusions in RR1000 at elevated temperature. Inclusion fracture and decohesion were observed within the first cycle of loading. Fatigue crack nucleation at the non-metallic inclusion coincided with that in an adjacent coarse grain containing a twin boundary. DDP modelling of the twin boundary showed the establishment of slip activation parallel as well as oblique to the interface, as observed in DIC characterisation. The DDP results showed pile-up driven generation of local GND density at the interface, in turn driving high local stored energy density and fatigue crack nucleation. These conditions were shown to result from the anisotropic elastic constraint at the twin boundary. In addition, the complex stress field arising from the agglomerate drives plasticity near the twin boundary contributing to the necessary conditions for fatigue crack nucleation.